2019
DOI: 10.1021/acs.iecr.9b02259
|View full text |Cite
|
Sign up to set email alerts
|

Boron Removal from Aqueous Solutions by Synthetic MgAlFe Mixed Oxides

Abstract: The boron removal capacity from an aqueous solution using MgAlFe mixed oxides from layered double hydroxides (LDH) was studied. They were synthesized by the coprecipitation method at 70 °C and were characterized as potential filter materials. The Fe3+ analyzed by X-ray photoelectron spectroscopy and UV–visible diffuse reflectance showed their tetrahedral and octahedral coordination. Scanning electron microscopy micrographs and thermogravimetric and differential scanning calorimetry analysis evidenced the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The research of De la Fuente et al [58] showed that the removal rate improved as the pH increased, presenting a maximum adsorption capacity at a pH value between 9.5 and 10.5. For an initial concentration of 50 mg/L, the maximum adsorption capacity was obtained after 30 min of stirring and 6 h of repose at 70 • C. Under these optimum conditions, a boron removal rate of around 95% was obtained; however, this value decreased to 75% at 30 • C. In a subsequent article [78], they demonstrated that the adsorption process followed a pseudo-second-order kinetic model and the Langmuir isotherm model. Nevertheless, the reaction process between boron and magnesium compounds was found to be irreversible, and neither pH nor temperature adjustment could be used to regenerate the adsorbents.…”
Section: Magnesium Oxidementioning
confidence: 90%
See 2 more Smart Citations
“…The research of De la Fuente et al [58] showed that the removal rate improved as the pH increased, presenting a maximum adsorption capacity at a pH value between 9.5 and 10.5. For an initial concentration of 50 mg/L, the maximum adsorption capacity was obtained after 30 min of stirring and 6 h of repose at 70 • C. Under these optimum conditions, a boron removal rate of around 95% was obtained; however, this value decreased to 75% at 30 • C. In a subsequent article [78], they demonstrated that the adsorption process followed a pseudo-second-order kinetic model and the Langmuir isotherm model. Nevertheless, the reaction process between boron and magnesium compounds was found to be irreversible, and neither pH nor temperature adjustment could be used to regenerate the adsorbents.…”
Section: Magnesium Oxidementioning
confidence: 90%
“…Under these optimum conditions, a boron removal rate of around 95% was obtained; however, this value decreased to 75% at 30 °C. In a subsequent article [ 78 ], they demonstrated that the adsorption process followed a pseudo-second-order kinetic model and the Langmuir isotherm model. Nevertheless, the reaction process between boron and magnesium compounds was found to be irreversible, and neither pH nor temperature adjustment could be used to regenerate the adsorbents.…”
Section: Inorganic Adsorbents For Boron Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Among of which, adsorption has become one of the most effective methods due to its simple operation, high selectivity and low energy consumption. Currently, Study on boron adsorption has being focused on various absorbents, such as ion exchange resins, activated carbon, metal oxides and hydroxides, polymers, metal-organic frameworks (MOFs) and magnetic adsorbents [14][15][16][17][18], and each kind of these absorbents has its own advantage and disadvantage during boron removal process. The magnetic nanoparticles (MNPs) and their functional composites had embodied high boron adsorption e ciency, simple magnetic separation and easy regeneration because of their large surface area, strong magnetic property, low cost and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%